Cloud Expression Categories in Arabic: A Morphosemantic Approach - Azzah Mufidah; Alif Cahya Setyadi (Edusoshum : Journal of Islamic Education and Social Humanities, 2026)
This study aims to analyze categories of expressions related to clouds in the Arabic language through a morphological-semantic approach, with the goal of explaining the relationship between morphological structure and lexical meaning in the semantic domain of clouds. This study employs a qualitative approach based on a literature review. Data were collected from major classical Arabic dictionaries, namely  Majma’ al-Ma’ani, Fiqh al-Lugha wa Sirr al-Arab, and Lisan al-Arab, supplemented by relevant scholarly literature. The analysis was conducted by identifying word roots, morphological patterns, and semantic features of each linguistic unit to develop a systematic morphological-semantic classification. The results identified 29 linguistic units representing the concept of clouds in Arabic. These linguistic units were classified into four main categories: the stages of cloud formation and development, cloud shapes and their structural characteristics, atmospheric density and coverage, and rain clouds along with their associated weather phenomena.  The analysis also reveals that differences in morphological patterns result in systematic semantic differences, such that each linguistic unit can not only refer to cloud phenomena but also represent their developmental stages, shapes, locations, densities, and functions within the weather system. These results indicate that the Arabic lexical system reflects a close relationship between morphology and semantics in the description of natural phenomena and contributes to the development of the field of semantic morphology.